Proceedings 40th Annual 2006 International Carnahan Conference on Security Technology 2006
DOI: 10.1109/ccst.2006.313422
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Motionless Laser Scanning Architecture for Perimeter Security

Abstract: This paper descrbes a motionless laser scanning architecture consisting of few components and no moving parts. While laser scanning by beam deflection mechanisms hold many advantages over conventional bi-static IR sensors and radio and microwave frequency intruder detection, inherent flaws exist relating to the wear and tear of the deflecting mirror and its electro-mechanical driving components. In the proposd approach, many beams are generated in an ordered fashion from a custom designed optical resonator wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Time of flight pulse detection or continuous wave phase shift methods are used to derive range measurements. According to tests conducted to determine the feasibility of using laser scanning for perimeter protection (Sahba et al, 2006), it has been confirmed the capability of detecting humans and vehicles, with a maximum range of 25m and 80m respectively. The testing demonstrated large area coverage, the ability to determine intruder size, the definition of multiple detection zones, a good detection rate and low false alarm rate (Hosmer, 2004).…”
Section: Fig 7 a 1-d Circular Scanning Data Cyclementioning
confidence: 95%
See 1 more Smart Citation
“…Time of flight pulse detection or continuous wave phase shift methods are used to derive range measurements. According to tests conducted to determine the feasibility of using laser scanning for perimeter protection (Sahba et al, 2006), it has been confirmed the capability of detecting humans and vehicles, with a maximum range of 25m and 80m respectively. The testing demonstrated large area coverage, the ability to determine intruder size, the definition of multiple detection zones, a good detection rate and low false alarm rate (Hosmer, 2004).…”
Section: Fig 7 a 1-d Circular Scanning Data Cyclementioning
confidence: 95%
“…This example highlights those sometimes optical sensors matrixes are the better detectors because of their good sensitivity/resolution. Another laser tools for static perimeter control is Laser radar (LADAR) (Sahba et al, 2006), (Stutz, 2005). LADAR scanning is far advanced over conventional active infrared (AIR) sensing.…”
Section: Fig 7 a 1-d Circular Scanning Data Cyclementioning
confidence: 99%
“…Intrusion detection technologies have been widely used in safety protection of critical infrastructures such as banks, airports, nuclear power plants, military bases and other sensitive sites which require a very high level of security. Common intrusion detection technologies include laser scanners [1], [2], infrared sensors [3], [4], video mobile detectors (VMDs) [5], [6] and electronic fences [7], [8]. However, these technologies have the following defects: (1) Detection equipments such as electronic fences are usually exposed to the outside and vulnerable to intentional evasion and malicious destruction, so they have poor concealments.…”
Section: Introductionmentioning
confidence: 99%
“…However, these technologies have the following defects: (1) Detection equipments such as electronic fences are usually exposed to the outside and vulnerable to intentional evasion and malicious destruction, so they have poor concealments. (2) The adaptabilities of detection equipments to weather change and terrain environment are also weak. For example, changes in environment temperature and visibility caused by wind, rain, snow, fog, hail and day/night can seriously interfere with the detection effects of laser scanners, infrared sensors…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation